2014
DOI: 10.1016/j.pss.2014.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Properties of comet 9P/Tempel 1 dust immediately following excavation by deep impact

Abstract: We analyzed Deep Impact High Resolution Instrument (HRI) images acquired within the first seconds after collision of the Deep Impact impactor with the nucleus of comet 9P/Tempel 1.These images reveal an optically thick ejecta plume that casts a shadow on the surface of the nucleus. Using the 3D radiative transfer code HYPERION we simulated light scattering by the ejecta plume, taking into account multiple scattering of light from the ejecta, the surrounding nuclear surface and the actual observational geometry… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…Similar numbers were obtained from ground-based observations by Schleicher et al (2006) and Biver et al (2007). Our estimate (Nagdimunov et al 2014), possible only for a gravity controlled crater, was 3*10 7 kg. Notice also that a strength dominated crater should be formed quite quickly, within several seconds, whereas a gravity dominated crater would require hundreds of second for its formation (Richardson et al 2007) and the last fact is more consistent with the formation of the Deep Impact crater, specifically, in the MRI images (McLaughlin et al 2014b) we see no evidence of detachment of the ejecta from the nucleus surface even 12 minutes after impact, which is more consistent with continuous excavation of the nucleus material for a period longer than a couple of seconds after impact.…”
Section: Discussion: Crater Development and Depth Of The Excavated Masupporting
confidence: 87%
See 1 more Smart Citation
“…Similar numbers were obtained from ground-based observations by Schleicher et al (2006) and Biver et al (2007). Our estimate (Nagdimunov et al 2014), possible only for a gravity controlled crater, was 3*10 7 kg. Notice also that a strength dominated crater should be formed quite quickly, within several seconds, whereas a gravity dominated crater would require hundreds of second for its formation (Richardson et al 2007) and the last fact is more consistent with the formation of the Deep Impact crater, specifically, in the MRI images (McLaughlin et al 2014b) we see no evidence of detachment of the ejecta from the nucleus surface even 12 minutes after impact, which is more consistent with continuous excavation of the nucleus material for a period longer than a couple of seconds after impact.…”
Section: Discussion: Crater Development and Depth Of The Excavated Masupporting
confidence: 87%
“…Whereas high albedo may be associated with a higher abundance of ice and low albedo with a low ice abundance or domination of absorbing (perhaps carbonaceous) materials, the inhomogeneities in the optical depth are harder to explain unambiguously. Our radiative transfer modeling reported in Nagdimunov et al (2014) showed that, due to the fact that the optical depth is a function of the extinction cross-section multiplied by the number density, we can find a variety of combinations of extinction cross-section and number density that produce the same fit for the optical depth. The bands of low optical depth or azimuthal inhomogeneities in optical depth can be areas of lower bulk density of the material (due to higher porosity) or areas characterized by dust consisting of particles of smaller extinction crosssection.…”
Section: Discussionmentioning
confidence: 91%
“…11 The real image of the ejecta plume from the surface of comet 9P/Tempel 1 and its shadow on the surface taken by the Deep Impact High Resolution Instrument (left) and the simulated image of the ejecta plume and its shadow computed by radiative transfer computations (right). From Nagdimunov et al (2014) dominate the forward-scattering region, have not been incorporated in their model.…”
Section: Single Scatteringmentioning
confidence: 99%
“…Nagdimunov et al, 2014;Shalima et al, 2015). Nagdimunov et al (2014) have succeeded in modeling both an optically thick ejecta plume and its shadow on the surface of comet 9P/Tempel 1 produced and imaged by the Deep Impact mission (see Fig. 11).…”
Section: Multiple Scatteringmentioning
confidence: 99%
See 1 more Smart Citation